2018
DOI: 10.3390/en11113017
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Impacts of Oil Price on Inflation: An Empirical Study of African OPEC Member Countries

Abstract: This study investigates the asymmetric impacts of oil price changes on inflation in Algeria, Angola, Libya, and Nigeria. Three different kinds of oil price data were applied in this study: the actual spot oil price of individual countries, the OPEC reference basket oil price, and an average of the Brent, WTI, and Dubai oil price. Autoregressive distributed lag (ARDL) dynamic panels were used to estimate the short- and long-term impacts. Also, we partitioned the oil price into positive and negative changes to c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 38 publications
5
50
1
1
Order By: Relevance
“…Interestingly, the results are robust under an alternative measure of CO 2 emissions in both economies and validate the choice of the NARDL estimation as a useful tool for policy reforms. Aligned with recent literature [87][88][89], we also suggest that the related studies which have taken into account the traditional linear specification, such as ARDL, may review and extend the phenomena under a non-linear setting introduced in recent literature, for better policy input.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, the results are robust under an alternative measure of CO 2 emissions in both economies and validate the choice of the NARDL estimation as a useful tool for policy reforms. Aligned with recent literature [87][88][89], we also suggest that the related studies which have taken into account the traditional linear specification, such as ARDL, may review and extend the phenomena under a non-linear setting introduced in recent literature, for better policy input.…”
Section: Discussionsupporting
confidence: 59%
“…Al-Mosabbeh also recorded a positive effect of money supply on inflation in Syria. In addition, other studies have concluded this positive effect for example Jiranyakul (2009), Bozkurt (2014) and Bala and Chin (2018). However, our result came against the findings of Naeem et al (2014) who reported no co-integration relationship between money supply and inflation in Syria in the long-run.…”
contrasting
confidence: 94%
“…The data were obtained from the TCMB electronic data distribution system (EVDS). Among the variables used in the study, the economic growth variable is included in the model inspired from Hamilton (1983Hamilton ( , 2003, Mork et al (1994), Jimenez-Rodriguez and Sanchez 2005 2017and Bala & Chin (2018) from studies; and BIST100 index variable was included in the model, inspired by Papapetrou (2001) and Ono (2011) 's work. Another variables used in the study is the BIST industrial index variable and producer price index.…”
Section: Data Descriptionmentioning
confidence: 99%